1992
DOI: 10.1159/000247407
|View full text |Cite
|
Sign up to set email alerts
|

Menkes’ Disease: Report of a Case and Determination of Eumelanin and Pheomelanin in Hypopigmented Hair

Abstract: We report a male infant with Menkes’ disease who showed, at the age of 3 months, slow growth, hair abnormalities such as pili torti and white hair, and low levels of serum copper and ceruloplasmin. The exceptionally bright portions of his hair contained eumelanin and pheomelanin at levels only half those of normal Japanese controls. After subcutaneous administration of copper-histidinate for 2 months, his scalp hair changed to dark brown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In Menkes disease, mutations in the ATP7A gene are characterized by hypopigmentation, kinky hair, neurological deterioration and early death in childhood owing to inhibition of copper absorption in the intestine, which results in a systemic copper deficiency (Lutsenko et al, 2007;Tomita et al, 1992). Menkes disease patients die within their first few years of life, whereas OHS patients can remain alive until adulthood (Kodama et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Menkes disease, mutations in the ATP7A gene are characterized by hypopigmentation, kinky hair, neurological deterioration and early death in childhood owing to inhibition of copper absorption in the intestine, which results in a systemic copper deficiency (Lutsenko et al, 2007;Tomita et al, 1992). Menkes disease patients die within their first few years of life, whereas OHS patients can remain alive until adulthood (Kodama et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, loss-of-function mutants of DmATP7 generate larvae with phenotypes that are similar to both Wilson's and Menkes diseases (Norgate et al, 2006). For instance, DmATP7 -/Y larvae have hypopigmented mouth hooks and are short-lived (similar to Menkes disease symptoms), although they are extremely lethargic (akin to the movement disorder in Wilson's disease) (Cox, 1999;Norgate et al, 2006;Tomita et al, 1992). Our results demonstrate that conditional silencing of DmATP7 specifically in the gut recapitulates major features of Menkes disease, such as the reduced copper pool, severe neurodevelopmental defects and early mortality (Figs 2-4).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that skin sulfhydryi oxidase, a S-S cross-linking enzyme, catalyzes the formation of the disulfide bond from sulfhydryl groups during the keratinization process in skin [6,8]. It has been reported that activated skin sulfhydryl oxidase has 2 atoms of copper in one molecule [9].…”
Section: Discussionmentioning
confidence: 99%
“…7 Tomita et al reported a case of white scalp hair in an infant with Menkes disease who had low levels of eumelanin and pheomelanin; the discolouration resolved after the administration of copper histidinate. 8 A solitary case of nummular headache associated with focal hair heterochromia in a child has also been reported. 9 Three different types of hair heterochromia have been previously described: patchy, segmental and diffuse.…”
Section: Pramod Kumarmentioning
confidence: 95%